OPTIMALISASI PERENCANAAN PERAWATAN MESIN MIXER FARFLY DENGAN PENDEKATAN RISK-BASED MAINTENANCE - Azwar Hartanto; Rahmad Wisnu Wardana; Anissa Kesy Garside (Jurnal Teknik Mesin dan Pembelajaran, 2023)
PT XYZ operates as a paint manufacturing company, producing two types of products, namely wall paint and pool paint, based on distinct raw materials. Within the production process, the role of the farfly mixer machine holds significant importance, as it facilitates the crucial mixing and dispersion processes involved in paint manufacturing. Unfortunately, operational usage of the farfly mixer machines often leads to malfunctions, resulting in disruptive downtimes and potential financial losses for the company. Consequently, an enhancement of the machine maintenance planning is imperative, utilizing the risk-based maintenance methodology to ascertain risk estimations associated with machine failures, conduct risk evaluations, and devise appropriate maintenance plans. The assessment of risk estimations yields a significant risk value amounting to IDR 10,459,765 per month. The evaluation results reveal that the calculated risk value surpasses the acceptance criteria, specifically denoting 0.73% compared to the expected threshold of 0.60%. Consequently, based on this risk evaluation outcome, it becomes evident that maintenance planning is warranted, necessitating the formulation of a proposed maintenance plan. The proposed plan focuses on optimising component replacement intervals, primarily targeting components with a reliability value lower than 80%.